Anti-mafia initiatives in Germany (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
Current research suggests that the expansion of Italian mafia groups in Germany is taking place almost completely unnoticed, as neither the state and regional institutions, nor civil society and the media are giving sufficient attention to the issue. The purpose of the paper is to identify and map the numerous organizations and events that have taken place in recent years, in an attempt to analyse the dimension and the dynamics of the anti-mafia movement in Germany. Taken together, these results suggest that there are many individuals and groups that are doing something in the anti-mafia field, even if they are not always reaching an adequate level of efficacy.Keywords: Germany, Anti-mafia movement, Mafia? Nein, Danke! e.V., Anti-mafia education, Journalism